Fiber-optic sensor cable for simultaneous distributed measurement of multiple physical quantities : doctoral thesis - Bašić, Petar; Šipuš, Zvonimir (Zagreb : P. Bašić ; Fakultet elektrotehnike i računarstva, 2019)
Fiber optic sensor cable technology is a relatively new research area that combines a set of scientific and technical disciplines in order to meet distributed sensor systems needs and quality standards. This thesis discusses a particular fiber optic cable design with three tightly encapsulated fibers for multipurpose and multivalent sensing, presently commercialized for temperature, strain and acoustic measurements. Furthermore, it introduces a mechanism for birefringence change as a function of outer perturbations, such as pressure and cable bending, as a new capability and potential feature for future optical sensor products. The concept is based on using cable raw materials (optical fiber, stainless steel strips, matured manufacturing procedures) with standard geometries produced and commercialized in high volumes nowadays. It uses symmetrical elements only and it exploits the geometrical configuration of equilateral triangle with optical fibers in each vertex that are tight buffered within the stainless-steel tube. This results with unsymmetrical loading of the optical fibers when exposed to external hydrostatic pressure thus giving rise to the birefringence change in the optical fibers. In this way the hydrostatic pressure as external mechanical measurand is coupled with optical parameters inside the interior optical fibers hermetically closed inside the stainless-steel tube. The concept was first evaluated with the Finite Element Analysis (FEA) commercial software tool resulted in proving the concept and giving the insight into the magnitude of tube compression.

The prototype of the cable 1.24mm in diameter was manufactured and tested up to 1200bar in a 24m long high-pressure chamber, especially designed for such purposes, enabling both mechanical and optical characterization of the sensor cable. The polarimetric method was chosen to prove the concept of changing birefringence properties of optical fiber. Although non-linear and irreversible, it demonstrated a strong change in Stokes parameters during both, pressure increase as well as pressure decrease cycles. Furthermore, the high-pressure facility is further used for evaluation of tube compression without optical fibers. The compression of the tube 2.1mm in diameter and steel wall thickness of 0.4mm, steel grade 316L was measured and thus exhibited linear characteristics for the pressure range from 0 to 1200bar. Due to off-the-center positions of optical fibers, the construction has the intrinsic capability to measure cable bending. The information on bending is always available since there is always at least one fiber in the compression zone and one in the extension zone. The sensor fibers were interrogated with the Brillouin Optical Time Domain Analysis (BOTDA) interrogation method. For testing purpose, a 20m long sample was produced and arranged in a coil of different diameters, and BOTDA measurements demonstrated shift in Brillouin peak frequency for all three observed fibers. In this way it was confirmed that optical fibers 0.455mm in diameter, placed off-the center inside the stainless-steel tube of 1.25mm in diameter, can be used for fiber optic distributed pressure and/or cable bending evaluation using stimulated Brillouin scattering technique.
Keywords: optical fiber, fiber optic measurements, monitoring systems, distributed optical fiber sensor, fiber in metal tube (FIMT), pressure sensors, acoustic sensors, strain sensors, temperature sensors, Brillouin effect, Brillouin Optical Time Domain Analysis (BOTDA)
Svjetlovodna senzorska kabelska tehnologija je relativno novo područje istraživanja u kojoj se susreću i isprepleću niz znanstvenih i tehničkih disciplina sve da bi se zadovoljili tehnički zahtjevi i standardi kvalitete tzv. raspodijeljenih senzorskih mjernih sustava. U ovom radu razmatra se posebna kabelska konstrukcija sačinjena od triju stiješnjenih svjetlovoda u metalnoj cjevčici za višestruku namjenu te polivalentno mjerenje i detekciju koja se trenutno komercijalno koristi za mjerenje temperature i vlaka te akustička mjerenja. Ona nadalje predstavlja mehanizam promjene dvolomnosti kao funkcije perturbacije na vanjskom omotaču, kao što je tlak i savijanje kabela, kao mogućeg novog detektorskog mehanizma budućih svjetlovodnih senzora. Koncept se temelji na iskorištavanju kabelskih sirovina standardnih geometrija i masovne proizvodnje, kao što su optičko vlakno i čelične vrpce, te stabilne proizvodne metode. Koriste se samo simetrični elementi te se iskorištava geometrijska konfiguracija istostraničnog trokuta sa svjetlovodima postavljenim u njegovim vrhovima koji su stiješnjeni omotačem - čeličnom cjevčicom. To rezultira nesimetričnim opterećenjem optičkih vlakana kada su podvrgnuta vanjskom hidrostatičkom tlaku i time se uzrokuje promjena dvolomnosti u svjetlovodima.

Prototip kabela promjera 1.24 mm je proizveden i tlačno testiran do 1200 bara u 24-metarskoj tlačnoj komori, specijalno konstruiranoj za tu namjenu, koja omogućuje i optičku i mehaničku karakterizaciju svjetlovodnih kabela. Polarizacijska mjerna metoda izabrana je za dokazivanje koncepta promjene dvolomnosti u svjetlovodu. Premda nelinearna i ireverzibilna metoda je pokazala snažnu promjenu u Stokesovim parametrima kod povećanja i smanjenja vanjskog hidrostatskog tlaka. Visokotlačna komora se nadalje koristila za procjenu kompresije čelične cjevčice bez optičkih vlakana. Kompresija cjevčice kvalitete čelika 316L, promjera 2.4mm i debljine stijenke 0.4mm se mjerila na području tlaka od 0 do 1200 bara pri čemu se pokazala linearna ovisnost promjena promjera s promjenom tlaka. Zbog izvanosnog položaja svjetlovoda konstrukcija posjeduje intrinzičnu mogućnost za mjerenja radijusa savijanja kabela. Informacija o savijanju je u konstrukciji uvijek dostupna jer je barem jedno vlakno u kompresijskoj ili ekstenzijskoj zoni presjeka kabela. Senzorski svjetlovodi su ispitivani metodom analize stimuliranog Brillouinovog raspršenja u vremenskoj domeni (BOTDA). Za svrhe testiranja 20-metarski uzorak senzorskog kabela je savinut u namote različitih promjera savijanja pri čemu su BOTDA mjerenja pokazala različite pomake centralne Brillouinove frekvencije kod sva tri svjetlovoda. Na taj način se potvrdilo da se optička vlakna postavljena izvan osi presjeka kabela za 0.455mm i stiješnjena čeličnom cjevčicom promjera 1.24mm mogu upotrijebiti za određivanje raspodijeljenog tlaka kao i za određivanje promjera savijanja kabela koristeći se tehnikom stimuliranog Brillouinovog raspršenja.
Ključne riječi : svjetlovodi, svjetlovodna mjerenja, mjerni sustavi, distribuirani svjetlovodni senzori, svjetlovodi u metalnoj cjevčici (FIMT), senzori pritiska, akustički senzori, senzori naprezanja, temperaturni senzori, Brillouiov efekt, analiza Brillouinovg raspršenja u vremenskoj domeni (BOTDA)
Bibliografija str. 110-114.